Seed weight predicts seedling emergence, and extremely acid soil and low availability of Phosphorus are associated with poor plant performances in Lepidium meyenii Walpers (maca) - Lozano-Canales, A. (2019)
Lepidium meyenii Walpers (maca) is a Peruvian species cultivated in the high Andean region (ca. 4000 m.a.s.l.), highly praised for the nutritional properties of its hypocotyl. The benefits to human health and their relationship with the hypocotyl have been well investigated. However, few studies have addressed the factors affecting field crop performance and the improvement of agronomic practices. Here we evaluate the effect of soil properties (humidity, temperature, and fertility) and sowing method (ridge-furrow system and flat planting) on the biological performance of five seed accessions of maca in 6 experimental plots along an altitudinal gradient (3554–4442 m.a.s.l.). Plots located at both the lowest and highest altitudes had lower plant survival, vegetative growth, and hypocotyl size. Most of the differences among plots could be attributed to the acidity and the concentration of available phosphorus in the soil. In addition, low soil temperature and humidity negatively affected crop performance at different stages of plant development. The ridge-furrow system appeared to promote plant growth, although it did not favor plant survival under the unexpected climatic conditions experienced. Finally, seed weight was found to be a good predictor of seedling emergence and plant survival.